2013
DOI: 10.1080/09644016.2013.854967
|View full text |Cite
|
Sign up to set email alerts
|

Legitimacy building in weak institutional settings:climate change adaptation at local level in Denmark and Norway

Abstract: Local strategies for adaptation to climate change in Denmark and Norway are discussed. In both countries, the national impetus for local adaptation is weak; it is largely left to local actors to take the initiative. The dynamics of the different approaches to climate-change adaptation at the local level are illuminated. Using decision-making and learning theory, we present an analytical framework to examine four cases, two in Norway and two in Denmark, which represent two different responses, i.e. anticipatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 36 publications
(40 reference statements)
1
25
0
Order By: Relevance
“…Furthermore, in the last decade, Denmark has seen an increasing focus on climate change specifically, driven, e.g. by the UN 15th Conference of Parties (COP15) which was held in Copenhagen in 2009 (Wejs et al 2013). In Denmark, the responsibility for an EIA rests with the authorities, either municipal or state (as mentioned in Section 2), and the high focus on climate change could be influenced by the responsibilities that the authorities have for living up to international and national agreements and goals on reduction of CO 2 emissions.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, in the last decade, Denmark has seen an increasing focus on climate change specifically, driven, e.g. by the UN 15th Conference of Parties (COP15) which was held in Copenhagen in 2009 (Wejs et al 2013). In Denmark, the responsibility for an EIA rests with the authorities, either municipal or state (as mentioned in Section 2), and the high focus on climate change could be influenced by the responsibilities that the authorities have for living up to international and national agreements and goals on reduction of CO 2 emissions.…”
Section: Resultsmentioning
confidence: 99%
“…Wejs et al 2014), also referred to as policy entrepreneurs (Bassett and Shandas 2010;Bulkeley 2010;Kingdon 2002;Meijerink & Huitema 2010) or local champions (Carmin et al 2012). These entrepreneurs take up the role of mobilizing other actors and building legitimacy for climate adaptation (Wejs et al 2014) and can be positioned both inside and outside the municipal organization (Kingdon 2002). Institutional entrepreneurship is demonstrated by individuals as well as by collectives.…”
Section: The Identification Of Possible Stimuli For Climate Adaptatiomentioning
confidence: 99%
“…However, the approaches to adaptation vary considerably between municipalities (Rauken et al, 2014), often adaptation garners limited attention from the public (Hjerpe et al, 2014) and it is perceived to compete with other, more pressing planning concerns (Dannevig et al, 2012;Nilsson et al, 2012). Research has also shown that huge discrepancies exist between the extent municipalities in the Nordic countries are able to adapt (Amundsen et al, 2010;Dannevig et al, 2012;Glaas et al, 2010;Wejs et al, 2013), which also points toe weak coordination from the national government (Dannevig et al, 2013;Wejs et al, 2013).…”
Section: Introductionmentioning
confidence: 91%